Review of Maritime Transport 2003 - United Nations Conference on Trade; Development (United Nations, 2003)
Review of Maritime Transport identifies the main developments in world maritime transport and provides worldwide statistical data. This annual Review focuses on maritime activities in developing countries as compared with other groups of countries. It also looks at the correlation between the development of global trade and maritime transport activities in general. Regional developments in African economic and maritime transport are the subject of this year's special chapter.